Design and simulation analysis of an aerospace damper. Issue 1 (February 2020) - Wang, Q L; Wang, Q X; Jiang, H J; Lin, Y H; Zhou, X H
Abstract: In this paper, viscoelastic materials are used to attenuate vibration for the optical remote sensor and satellite base. Flexible-base single-degree-of-freedom vibration attenuate system model is built considering that the satellite base is not rigid. The transfer ratio of the vibration damping system when the satellite platform foundation is non-rigid is obtained by using the four-terminal parameter method and the mechanical impedance method. Furthermore, the effects of mass ratio, fundamental frequency ratio, basic damping ratio and damper damping ratio on the vibration attenuate efficiency are discussed. According to the properties of integrated space optical remote sensor and satellite base, the optimum parameter combination between damping ratio and vibration attenuate efficiency is obtained. The design schemes of the viscoelastic material damper are refined using the simulation analysis results.